POSSIBILITIES OF PREVENTION OF ALLERGIC DISEASES TAKING INTO ACCOUNT REGIONAL PECULIARITIES - Перевощикова, Нина Константиновна; Гладков, Сергей Федорович; Черных, Наталья Степановна (Mother and Baby in Kuzbass, 2017)
The increasing growth of allergic diseases is pandemic. The International Study of Asthma and Allergies in Childhood (ISAAC) has discovered high frequency variability of symptoms of bronchial asthma (BA) and atopic dermatitis (AtD) even within one country due to climatic, environmental factors, lifestyle and condition of healthcare system. The accomplishments concerning the treatment of BA and AtD, that were achieved during the last few years and were regulated by the list of consensus documents, did not assist the decrease of their prevalence. The ability to protect a child, who predisposed to atopy from the exposure to precipitating factors, helps to prevent its realization in the phenotype of allergic diseases. The prevention of allergic diseases must be provided with a variety of measures and carried out at all stages of human life from prenatal period.The aim – the decrease of allergic diseases frequency among children.Materials and methods. The researches were conducted in 3 stages. At the first stage there were discovered the features of development of BA in children living in Yurga, Kemerovo region, and there was studied the importance of ecological factors of the environment. At the second stage, taking into account the peculiarities of the development and course of BA, the children with AtD were examinedand sent for treatment aimed at the prevention of AtD transformation into BA. At the third stage within the framework of «Atopy School» there was developed a complex of pre- and postnatal prevention of allergic diseases in children at risk.The results. Regional characteristics of Yurga contribute to the realization of AD incidence in children with hereditary predisposition. There was proved the role of opportunistic pathogenic microflora in the development of AtD (70 %), there was also confirmed the dependence of clinical symptoms from the bacteria type. There was developed a program of managing children with atopic dermatitis involving sanitation of bowel using specialized bacteriophages. There was also created «Atopy School» program of managing women with the atopic disease, which works according to the «woman ®pregnant ® fetus ® newborn ® child» principle and provides primary prevention of atopic disease in children at risk.Conclusion. The implementation of the program of secondary and primary prevention of atopic diseases has reduced the AtD and BA prevalence among children.
Keywords: allergic diseases; atopic march; atopic dermatitis; bronchial asthma; opportunistic microflora; children; case rate; prophylaxis of allergic diseases